Effects of surfactant structure on the phase inversion of emulsions stabilized by mixtures of silica nanoparticles and cationic surfactant - Cui, Z-G (Langmuir : the ACS journal of surfaces and colloids, 2010)
Silica nanoparticles without any surface modification are not surface active at the toluene-water interface due to their extreme hydrophilicity but can be surface activated in situ by adsorbing cationic surfactant from water. This work investigates the effects of the molecular structure of water-soluble cationic surfactant on the surface activation of the nanoparticles by emulsion characterization, adsorption and zeta potential measurements, dispersion stability experiments, and determination of relevant contact angles. The results show that an adsorbed cationic surfactant monolayer on particle surfaces is responsible for the wettability modification of the particles. In the presence of a trace amount of cationic surfactant, the hydrophobicity of the particles increases, leading to the formation of stable oil-in-water O/W(1) emulsions. At high surfactant concentration (>cmc) the particle surface is retransformed to hydrophilic due to double-layer or hemimicelle formation, and the concentration of the free surfactant in the aqueous phase is high enough to stabilize emulsions alone. O/W(2) emulsions, probably costabilized by free surfactant and particles, are then formed. The monolayer adsorption seems to be charge-site dependent. Thus, using single-chain trimethylammonium bromide surfactants or a double-head gemini cationic surfactant, the hydrophobicity of the particles achieved is not sufficient to stabilize water-in-oil (W/O) emulsions, and no phase inversion is induced. However, using a double-chain cationic surfactant, the chain density on the particle surfaces endows them with a hydrophobicity high enough to stabilize W/O emulsions, and double phase inversion, O/W(1) --> W/O --> O/W(2), can then be achieved by increasing the surfactant concentration